Thank You to Our 2019 Reviewers - Noé Lugaz; Delores J. Knipp; Jennifer L. Gannon; Michael Hapgood; Huixin Liu; T. Paul O'Brien; Daniel T. Welling (Space Weather)
Abstract Peer reviewing is the foundation of modern scholarship, with external specialists being asked to fairly check and evaluate submitted work. This difficult and often time‐consuming activity is performed voluntarily, with the understanding that one's own scholarship shall benefit down the line from a careful analysis of its assumption, results, accuracy, and yes, language, as we are now evaluating someone else's work. At Space Weather, we pride ourselves on a fair but quick review process yielding high‐quality articles with a time from submission to first decision of under one month. This would not be possible without the hard work of all our reviewers. Once a year, we take the occasion to name these women and men in order to thank them for their service to the journal and the community.